Patronage and Indebtedness: Portugal, Castile and the Papal Court around the Year 1300. - Linehan, Peter (Historia. Instituciones. Documentos, 2018)
ABSTRACT: Based on previously unexamined documentation at Lisbon, Braga and the Vatican, this paper considers two separate but related matters for the history of Portugal: the role of Cardinal Giacomo Colonna in the foundation of the Lisbon Studium Generale, and the use of Portuguese gold at the court of Pope Boniface VIII to purchase the dispensation for the marriage of Fernando IV of Castile to Constança of Portugal. It also demonstrates the bankrupt state of the Castilian crown after ten years of Fernando IV’s rule. RESUMEN: A partir de documentación hasta ahora no estudiada, conservada en Lisboa, Braga y el Vaticano, en este artículo se analizan dos asuntos diferentes aunque relacionados, referentes a la historia de Portugal: el papel desempeñado por el Cardenal Giacomo Colonna en la fundación del Studium Generale de Lisboa y el uso del oro portugués en la corte del papa Bonifacio VIII para obtener la dispensa para que pudiese efectuarse el matrimonio entre Fernando IV de Castilla con Constanza de Portugal, hija del rey D. Dinis. Esto demuestra también el estado de bancarrota de la corona castellana después de diez años de gobierno de Fernando IV.